Method for improving Zeta potential and sanding effect of sanding slurry

The titanium dioxide impurity ions are removed by hot-beating water washing and adjusting the pH value, which improves the Zeta potential of the titanium dioxide slurry, solves the problems of slurry dispersion and sanding effect, and achieves the uniformity of the titanium dioxide coating and product performance.

CN119633971AActive Publication Date: 2025-03-18JIANGSU TOP FINE NEW RAW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311481510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2025-03-18
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

The prior art is difficult to maintain its dispersion while increasing the concentration of titanium dioxide slurry, resulting in poor sanding effect and affecting the uniformity of the titanium dioxide coating and product performance.

Method used

The titanium dioxide impurity ions are removed by hot-beating water washing, and the pH value of the titanium dioxide slurry is adjusted to improve the zeta potential of the slurry, thereby improving its dispersion and sanding effect.

Benefits of technology

The high Zeta potential of high concentration sand agrinding slurry is achieved, which improves its dispersion and sand agrinding effect, and ensures the uniformity of the titanium dioxide coating and the improvement of product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633971A_ABST
    Figure CN119633971A_ABST
Patent Text Reader

Abstract

The invention discloses a method for increasing Zeta potential of sanding slurry, which comprises the following steps: S1, putting deionized water into a beaker, stirring, slowly adding coarse powder titanium dioxide, and then adding deionized water to prepare titanium dioxide slurry with the weight percentage concentration of 21.16-30.85%; s2, slowly heating the titanium dioxide slurry prepared in the step S1, curing, carrying out suction filtration to obtain a filter cake, washing with water, and pressing to remove redundant water in the filter cake by using a regulating cutter; and S3, adding water into the filter cake subjected to water removal by pressure in the step S2, pulping to prepare high-concentration sanding slurry, dropwise adding a sodium hydroxide solution to control the pH value of the sanding slurry to be 6-9, and sanding the sanding slurry in a polyurethane sanding tank. According to the method, the titanium dioxide slurry is subjected to hot pulping and water washing treatment, so that all impurity ions are removed, the Zeta value of the sanding slurry with high concentration is at a high potential, and the dispersity of the titanium dioxide slurry is improved; the particle size of the sanding slurry is uniform, and the sanding effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium dioxide, in particular to a method for improving the Zeta potential of sand-grinding slurry and the sand-grinding effect. Background Art

[0002] In the production process of rutile titanium dioxide by the sulfuric acid method, the coarse titanium dioxide powder needs to be sand-milled before the titanium dioxide coating can be carried out. The reasons are: (1) The primary particles grown during the calcination process are very small, have a high specific surface energy, are extremely unstable, and quickly agglomerate at high temperatures. After initial crushing, the particle surface has uneven defects, but the particles after sand-milling are spherical, have no edges and corners, and have a more concentrated particle size distribution.

[0003] (2) After calcining, the coarse particles of titanium dioxide will still have a certain amount of 1-10 micron coarse particles or aggregated particles that are not pulverized even after being crushed by Raymond mill. It takes a lot of energy to separate them. Sand milling can crush the aggregated particles and agglomerated particles of the calcined product.

[0004] (3) The most ideal state of titanium dioxide coating is to coat each single particle with the coating agent. Only in this way can each particle be guaranteed to have a coating layer when the air flow is crushed after coating, thereby achieving the purpose of surface treatment coating. If TiO2 is not ground and dispersed before coating, it is possible to coat the aggregated particles or flocculated particles. After the air flow is crushed, the coating layer of this coating material is broken, presenting an incomplete coating state, which cannot achieve the expected purpose of coating. Therefore, sand grinding must be performed before coating to make the final product have pigment properties.

[0005] Coarsely crushed titanium dioxide needs to be slurried before sand milling, and the slurry after slurrying can be in a dispersed state. The better the slurry is dispersed, the better the sand milling effect is; the worse the slurry is dispersed, the worse the sand milling effect is. The slurry dispersion effect is measured by the zeta potential of the slurry. The higher the zeta potential (when the absolute value of the zeta potential exceeds 70°C, the zeta potential is high), the better the slurry dispersion effect is and the better the sand milling effect is; the lower the zeta potential is, the worse the slurry dispersion effect is and the worse the sand milling effect is, resulting in uneven coating on the particle surface, and even some particles cannot be coated, thus affecting the application performance of the product. Therefore, it is of great significance to study the factors affecting the zeta potential of the slurry.

[0006] The value of Zeta potential is related to the dispersion of the system. The higher the absolute value of Zeta potential, the more stable the system. The lower the absolute value of Zeta potential, the more the system tends to cohere, that is, the attractive force exceeds the repulsive force. The factors affecting Zeta potential are as follows:

[0007] (1) Slurry pH

[0008] If the particles in the slurry are negatively charged, adding alkali will make it more difficult for the particles to be positively charged. If acid is added, the initial charge of the particles will be neutralized, and further addition of acid will gradually make the particles more positively charged. In the correlation curve between Zeta potential and pH value, the potential is positive at low pH points and negative at high pH points. There is a point on the curve that passes through the Zeta zero potential, which is called the isoelectric point. The slurry at the isoelectric point has poor dispersibility and is in a thickened state, and the sanding effect is very poor.

[0009] (2) Influence of impurity ions

[0010] According to the double layer theory, the double layer of particles with negative charges on the surface will be compressed by anions or cations in the system, resulting in a decrease in the slurry potential and a decrease in the dispersibility of the titanium dioxide slurry. A large amount of impurity ions, such as SO4, are introduced during the production of rutile titanium dioxide. 2- , K + Plasma, so it is necessary to remove these impurities before sanding to make the Zeta of the slurry at a high potential.

[0011] To achieve the best state of sand grinding, it is necessary to ensure that the slurry concentration entering the sand mill is high and the slurry dispersion is good. However, the increase in the concentration of titanium dioxide slurry will reduce the Zeta potential, resulting in poor slurry dispersion. How to increase the slurry concentration while not reducing the slurry dispersion has always been a technical problem in the industry. At present, in terms of improving the dispersion of titanium dioxide slurry, many titanium dioxide manufacturers use methods to optimize the pulping process, such as adding an appropriate amount of dispersant, sodium hexametaphosphate, sodium silicate and polycarboxylates, etc. The addition of the above chemical reagents is bound to have an adverse impact on the environment.

[0012] In the method of reducing the viscosity of titanium dioxide slurry in patent CN105921212A, the titanium dioxide primary product is ground and then graded through a standard sieve, the material under the sieve is pulped and dispersed, the material on the sieve is re-ground, the fineness of the titanium dioxide primary product is controlled by roller milling, and the concentration of the titanium dioxide slurry is increased by changing the fineness of the pulped material. This method uses high energy consumption of roller milling, and controls the fineness by grading and re-grinding, which increases the cost. Summary of the invention

[0013] The technical problem to be solved by the present invention is to provide a method for improving the Zeta potential of sand-grinding slurry and the sand-grinding effect in view of the shortcomings of the prior art. The method removes impurity ions of titanium dioxide by hot beating water washing, and adjusts the pH value of titanium dioxide slurry to improve the Zeta potential of the slurry. The sand-grinding effect is characterized by the particle size parameter of the sand-grinding slurry. The narrower the particle size distribution of the sand-grinding slurry, the more uniform the particle size of the sand-grinding slurry.

[0014] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for improving the Zeta potential of sand grinding slurry, which specifically includes the following steps:

[0015] S1: Put deionized water in a beaker, stir, slowly add the preliminarily crushed titanium dioxide, and then add deionized water to prepare a titanium dioxide slurry with a weight percentage concentration of 21.16-30.85%;

[0016] S2: slowly heating the titanium dioxide slurry obtained in step S1, aging it, filtering it to obtain the S1 filter cake, washing it with water, and pressing out the excess water from the filter cake with a spatula;

[0017] S3: The filter cake from which the water is pressed out in step S2 is slurried with water to prepare a sand-grinding slurry with a weight percentage concentration of 51.77-59.92%, sodium hydroxide solution is added dropwise to control the pH value of the sand-grinding slurry to be 6-9, and the sand-grinding slurry is placed in a polyurethane sand-grinding tank for sand-grinding.

[0018] In a preferred embodiment of the present invention, the weight percentage concentration of the titanium dioxide slurry in step S1 is 21.16-30.85%, preferably 23.25-27.8%. If the concentration of the titanium dioxide slurry is too low, the efficiency of pulping and washing is low; if the concentration of the titanium dioxide slurry is too high, the viscosity is too high and the material is not stirred evenly.

[0019] In a preferred embodiment of the present invention, the titanium dioxide slurry in step S2 is slowly heated to 50-80°C, preferably 55-65°C, at a rate of 1-2°C / min. In the present invention, the heating rate of the titanium dioxide slurry cannot be too fast or too slow. If the heating rate is too slow, the efficiency is too low. If the heating rate is too fast, the local material temperature is high and the material will stick to the wall. When the temperature of the titanium dioxide slurry after heating is less than 50°C, the impurity ions attached to the surface of TiO2 cannot be completely diffused into the titanium dioxide slurry, affecting the work efficiency. When the temperature of the titanium dioxide slurry after heating is greater than 80°C, the titanium dioxide slurry sticks to the wall and wastes heat energy. The impurity ions in the titanium dioxide slurry that sticks to the wall cannot diffuse into the slurry, and this part of the impurity ions cannot be effectively removed.

[0020] In a preferred embodiment of the present invention, the aging time in step S2 is 0.5 to 2 hours, preferably 1 hour. When the aging time is less than 0.5 hours, the impurity ions on the surface of TiO2 are not completely diffused into the titanium dioxide slurry. The technicians of the present invention detected that when the aging time of the titanium dioxide slurry is 10 minutes, 95% of the impurity ions on the surface of TiO2 have basically diffused into the slurry; when the aging time of the titanium dioxide slurry is 30 minutes, 99.5% of the impurity ions on the surface of TiO2 have basically diffused into the slurry.

[0021] In a preferred embodiment of the present invention, deionized water is used for washing in step S2. During washing, the weight ratio of titanium dioxide slurry (in terms of TiO2) to deionized water is 1:1-5, preferably 1:2-3. If the amount of deionized water is too little during washing, the impurity ions on the surface of titanium dioxide are not completely removed; when the weight ratio of titanium dioxide slurry (in terms of TiO2) to deionized water is 1:1-5, preferably 1:2-3 during washing, the soluble impurity ions can all be diffused into the titanium dioxide slurry. If the amount of water during washing is too high, it will cause waste of resources.

[0022] The titanium dioxide slurry of the present invention is treated by hot beating and water washing, and the impurity ions attached to the surface of TiO2 are basically completely diffused into the titanium dioxide slurry, and the impurity ions of titanium dioxide are removed. The dispersibility of the titanium dioxide slurry is good. The weight percentage concentration of the sand-milled slurry in step S3 is 51.77-59.92%, and a good sand-milling effect can be achieved without adding a dispersant or only adding 0.01-0.03% of a dispersant. The titanium dioxide slurry that has not been treated by hot beating and water washing has a lot of impurity ions attached to the surface of TiO2, resulting in poor dispersibility of the titanium dioxide slurry. It is necessary to add 0.2-0.5% of sodium hexametaphosphate, sodium silicate, and polycarboxylate and other dispersants, so that the mass percentage concentration of the sand-milled slurry can be controlled at 36.41-43.67%. The concentration of the sand-milled slurry is low, and the sand-milling effect is not good.

[0023] In a preferred embodiment of the present invention, the Zeta potential of the sand-grinding slurry in S3 is -70 to -85 mv, and the Zeta potential of the sand-grinding slurry is a high potential.

[0024] To achieve the best sand grinding state, it is necessary to ensure that the slurry concentration entering the sand mill is high and the slurry dispersibility is good. However, the increase in the concentration of titanium dioxide slurry will reduce the Zeta potential, resulting in poor dispersibility of the slurry. High titanium dioxide slurry concentration and good dispersibility are contradictory. Therefore, the present invention removes all impurity ions by hot beating and washing the titanium dioxide slurry, so that the Zeta value of the high-concentration sand grinding slurry is at a high potential, thereby improving the dispersibility of the titanium dioxide slurry.

[0025] The present invention uses a polyurethane sand milling jar for sanding because the sand milling jar has good wear resistance.

[0026] In a preferred embodiment of the present invention, the speed of sand milling in step S3 is 3500-4500 rpm, and the sand milling time is 50-80 min. If the speed of sand milling is too low, the titanium dioxide has few chances to collide with the zirconium beads and the titanium dioxide particles, the sand milling effect cannot be achieved, and the particle size of the sand milling slurry will be coarse; if the speed of sand milling is too high, a large amount of heat will be generated, and the zirconium beads will be ground and crushed in large quantities and mixed in the slurry, which will affect the quality of the product and increase the production cost.

[0027] The present invention also discloses a method for improving the sanding effect by improving the Zeta potential of the sanding slurry. The sanding effect is characterized by the parameters of the particle size of the sanding slurry, mainly by the parameter of D50. When the value of D50 reaches a certain requirement, the parameter of the diameter-to-span ratio is used as a characterization index. The D50 of the sanding slurry is 0.3-0.4 μm, the diameter-to-span ratio is 1.2-1.5, and the particle size of the sanding slurry is more uniform.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The invention removes all impurity ions by hot beating and water washing treatment of titanium dioxide slurry, makes the Zeta value of high-concentration sand-grinding slurry at a high potential, and improves the dispersibility of titanium dioxide slurry.

[0030] The present invention also provides a method for improving the sanding effect by increasing the Zeta potential of the sanding slurry. The sanding effect is characterized by the particle size parameters of the sanding slurry. The diameter-to-width ratio of the sanding slurry is 1.2-1.5, and the D50 is 0.3-0.4 μm. D50 represents the particle size at which the cumulative distribution of particles is 50%. The diameter-to-width ratio represents the width of the particle size distribution of the sanding slurry. The smaller the diameter-to-width ratio value, the narrower the particle size distribution of the sanding slurry, and the more uniform the particle size of the sanding slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the particle size parameter of the sand-grinding slurry in Example 1 of the present invention;

[0032] Figure 2 is the particle size parameter of the sand-grinding slurry in Example 2 of the present invention;

[0033] Figure 3 is the particle size parameter of the sand-grinding slurry in Example 3 of the present invention;

[0034] Figure 4 is the particle size parameter of the sand-grinding slurry in Comparative Example 1 of the present invention;

[0035] Figure 5 is the particle size parameter of the sand-grinding slurry in Comparative Example 2 of the present invention;

[0036] Figure 6 is the particle size parameter of the sand-grinding slurry in Comparative Example 3 of the present invention;

[0037] Figure 7 This is a photograph of the high Zete potential of Example 1-Example 3. DETAILED DESCRIPTION

[0038] The slurry Zeta potential was detected using an American colloidal dynamics high-concentration Zeta potential analyzer (model Zetaprobe).

[0039] In order to facilitate the test and ensure accurate measurement, the test process was carried out by weighing. The slurry concentration in the embodiment is expressed in weight percentage.

[0040] The inventors have found through numerous experiments that the percentage concentration corresponds to the slurry concentration unit of g / l

[0041] The fitting formula is Where x is the titanium dioxide slurry g / l, and Y is the weight percentage concentration.

[0042] Example 1

[0043] (1) 1000 ml of deionized water was placed in a glass beaker, stirring was started, 350 g of a titanium dioxide coarse powder sample was slowly added, and then 200 ml of water was added to prepare a titanium dioxide slurry with a weight percentage concentration of 22.58%; the pH of the titanium dioxide slurry was adjusted to 8.5, and the Zeta potential of the titanium dioxide slurry was measured by a colloidal dynamics high concentration Zeta potential analyzer, and the Zeta was -35.3 mv.

[0044] (2) The titanium dioxide slurry was slowly heated to 60° C. and aged for 60 minutes. The titanium dioxide slurry was filtered using a Buchner funnel to obtain a filter cake. 800 ml of deionized water was added to wash the filter cake. Excess water was removed from the filter cake using a spatula.

[0045] (3) The filter cake from which water has been pressed out is slurried with water to prepare a sand-grinding slurry with a weight percentage concentration of 56.9%, and sodium hydroxide solution is added dropwise to adjust the pH of the sand-grinding slurry to 8.5. The Zeta of the sand-grinding slurry is measured by a colloidal dynamics high concentration Zeta potential analyzer and is -80.5 mv.

[0046] (4) The sand-ground slurry was placed in a sand-ground jar and sand-ground at a speed of 4000 rpm for 1 hour. The particle size of the sand-ground slurry was measured by a Bettersize 3000 particle size distribution instrument, and the diameter-to-pitch ratio was 1.29, D10: 0.182 μm, D50: 0.360 μm, and D90: 0.647 μm (e.g. Figure 1 shown).

[0047] D10 represents the particle size at which the cumulative distribution of particles is 10%, D50 represents the particle size at which the cumulative distribution of particles is 50%, and D90 represents the particle size at which the cumulative distribution of particles is 90%; the diameter-to-width ratio = (D90-D10) / D50, which represents the width of the particle size distribution. The smaller the diameter-to-width ratio, the narrower the particle size distribution of the sand-grinding slurry, and the more uniform the particle size of the sand-grinding slurry.

[0048] Example 2

[0049] Steps (1) to (2) are the same as those in Example 1

[0050] (3) The filter cake from which water has been pressed out is slurried with water to prepare a sand-grinding slurry with a weight percentage concentration of 56.9%, and sodium hydroxide solution is added dropwise to adjust the pH of the sand-grinding slurry to 9.0. The Zeta of the sand-grinding slurry is measured by a colloidal dynamics high concentration Zeta potential analyzer and is -81.2 mv.

[0051] (4) The sand-ground slurry was placed in a sand-ground jar and sand-ground at a speed of 4000 rpm for 1 hour. The particle size of the sand-ground slurry was measured using a Bettersize 3000 particle size distribution instrument. The diameter-to-pitch ratio was 1.50, D10: 0.205 μm, D50: 0.394 μm, and D90: 0.796 μm (e.g. Figure 2 shown).

[0052] Example 3

[0053] Steps (1) to (2) are the same as those in Example 1

[0054] (3) The filter cake from which water is pressed out is slurried with water to prepare a sand-grinding slurry with a weight percentage concentration of 56.9%, and sodium hydroxide solution is added dropwise to adjust the pH of the sand-grinding slurry to 7.5. The Zeta of the sand-grinding slurry is measured by a colloidal dynamics high concentration Zeta potential analyzer and is -75.5 mv.

[0055] (4) The sand-ground slurry was placed in a sand-ground jar and sand-ground at a speed of 4000 rpm for 1 hour. The particle size of the sand-ground slurry was measured by a Bettersize 3000 particle size distribution instrument, and the diameter-to-pitch ratio was 1.421, D10: 0.203 μm, D50: 0.387 μm, and D90: 0.753 μm (e.g. Figure 3 shown).

[0056] Comparative Example 1

[0057] (1) 265 ml of deionized water was placed in a glass beaker, stirring was started, and 350 g of a titanium dioxide coarse powder sample was slowly added to prepare a titanium dioxide slurry with a weight percentage concentration of 56.9%; the pH of the titanium dioxide slurry was adjusted to 8.5, and the Zeta of the titanium dioxide slurry was measured by a colloidal dynamics high concentration Zeta potential analyzer to be -25.3 mv.

[0058] (2) Place the titanium dioxide slurry in a sand mill and sand grind it at a speed of 4000 rpm for 1 hour. The titanium dioxide slurry that has not been hot-beaten and washed has a lot of impurity ions attached to the surface of TiO2 and a low Zeta potential value, resulting in poor dispersion of the titanium dioxide slurry. The particle size grinding effect of the sand milled slurry is very poor and the particle size is very coarse. The particle size of the slurry is tested using a Bettersize 3000 particle size distribution instrument, and its diameter-to-width ratio is 1.975, D10: 0.799μm, D50: 1.419μm, D90: 3.602μm (such as Figure 4 shown).

[0059] In the comparative example, the Zeta potential of the titanium dioxide slurry is low, the dispersibility of the slurry is poor, the sand grinding effect is poor, and the D50 value is high. When the D50 value exceeds 0.5 μm, the particle size of the sanded slurry is very coarse. At this time, it is meaningless to use the parameter of the diameter-to-width ratio as a characterization index.

[0060] Comparative Example 2

[0061] (1) Take 265 ml of deionized water and place it in a glass beaker. Start stirring and slowly add 350 g of titanium dioxide coarse powder sample to prepare a titanium dioxide slurry with a weight percentage concentration of 56.9%. Then add 0.3% dispersant sodium hexametaphosphate and stir for 30 minutes. The pH of the titanium dioxide slurry is adjusted to 8.5. The Zeta of the titanium dioxide slurry is measured by a colloidal dynamics high concentration Zeta potential analyzer and is -35.3 mv.

[0062] (2) Place the titanium dioxide slurry in a sand mill and sand grind it at a speed of 4000 rpm for 1 hour. In Comparative Example 2, a dispersant was added, and the Zeta potential of the titanium dioxide slurry was improved compared with that in Comparative Example 1. However, compared with Examples 1-3, the titanium dioxide slurry was not treated with hot beating and water washing. The titanium dioxide slurry that was not treated with hot beating and water washing had a lot of impurity ions attached to the surface of TiO2, and the Zeta potential value was still very low, resulting in poor dispersibility of the titanium dioxide slurry, poor particle size grinding effect of the sand milled slurry, and very coarse particle size. The particle size of the slurry was detected using a Bettersize 3000 particle size distribution instrument, and its diameter-to-span ratio was 3.17, D10: 0.502μm, D50: 0.971μm, D90: 3.582μm (such as Figure 5 shown).

[0063] Comparative Example 3

[0064] (1) 550 ml of deionized water was placed in a glass beaker, stirring was started, and 350 g of a titanium dioxide coarse powder sample was slowly added to prepare a titanium dioxide slurry with a weight percentage concentration of 38.9%, and then 0.3% sodium silicate was added and stirred for 30 minutes.

[0065] (2) The pH value of the titanium dioxide slurry was adjusted to 8.5, and the Zeta potential of the titanium dioxide slurry was measured by a colloidal dynamics high concentration Zeta potential analyzer to be -50.5 mv.

[0066] (3) The titanium dioxide slurry was placed in a sand mill and sanded at a speed of 4000 rpm for 1 hour. The particle size of the slurry was measured using a Bettersize 3000 particle size distribution instrument, and the diameter-to-width ratio was 2.0, D10: 0.181 μm, D50: 0.570 μm, and D90: 1.321 μm (e.g. Figure 6 shown).

Claims

1. A method for increasing the Zeta potential of a sand-grinding slurry, characterized in that: It includes the following steps: S1: Put deionized water in a beaker, stir, slowly add coarse powdered titanium dioxide, and then add deionized water to prepare a titanium dioxide slurry with a weight percentage concentration of 21.16-30.85%; S2: slowly heating the titanium dioxide slurry obtained in step S1, aging it, filtering it to obtain a filter cake, washing it with water, and pressing out excess water from the filter cake with a spatula; S3: The filter cake from which the water is pressed out in step S2 is slurried with water to prepare a sand-grinding slurry with a weight percentage concentration of 51.77-59.92%, sodium hydroxide solution is added dropwise to control the pH value of the sand-grinding slurry to be 6-9, and the sand-grinding slurry is placed in a polyurethane sand-grinding tank for sand-grinding.

2. A method for increasing the Zeta potential of sand grinding slurry according to claim 1, characterized in that: In step S2, the titanium dioxide slurry is slowly heated to 50-80°C, preferably 55-65°C, at a rate of 1-2°C / min.

3. A method for increasing the Zeta potential of sand grinding slurry according to claim 1, characterized in that: The aging time in step S2 is 0.5 to 2 hours, preferably 1 hour.

4. A method for increasing the Zeta potential of sand grinding slurry according to claim 1, characterized in that: In step S2, deionized water is used for washing. During washing, the weight ratio of titanium dioxide slurry (calculated as TiO2) to deionized water is 1:1-5, preferably 1:2-3.

5. A method for increasing the Zeta potential of sand grinding slurry according to claim 1, characterized in that: The zeta potential of the sand-grinding slurry in step S3 is -70 to -85 mv.

6. A method for increasing the Zeta potential of sand-grinding slurry according to claim 1, characterized in that: The rotation speed during sand grinding in step S3 is 3500-4500 rpm, and the sand grinding time is 50-80 min.

7. A method for improving sand grinding effect by increasing the Zeta potential of sand grinding slurry according to any one of claims 1 to 6, characterized in that: The sanding effect is characterized by the sanding slurry particle size parameters. The diameter ratio of the sanding slurry is 1.2-1.5, and D50 is 0.3-0.4 μm.

Citation Information

Patent Citations

  • Method for reducing viscosity of titanium dioxide slurry

    CN105921212A

  • Method for preparing nano titanium dioxide water-dispersion liquid

    CN101367547A

  • High-purity ultra-fine titanium dioxide prepared from industrial metatitanic acid and preparation method of titanium dioxide

    CN106365200A

  • Method for preparing slurry titanium dioxide by hydrothermal method

    CN111019401A

  • Preparation method of special titanium dioxide for high-gloss ink

    CN115594994A